Understanding the issues of failure to pay life insurance claims: A perspective on absolute responsibility at PT. Jiwasraya - Purwanto Purwanto; Muhammad Doing; Riduwan Riduwan (Institute Of computer Science (IOCS), 2024)
The purpose of this study is to examine the principle of absolute responsibility as it is used in Indonesian statutes, with a focus on how it impacts the legal liability of business actors, in particular insurance firms, when it comes to the nonpayment of claims made by policyholders. Using primary, secondary, and tertiary sources together with legal hermeneutics analysis, the technique used is normative juridical with a statutory approach. This study's findings suggest that insurance firms' legal liability is affected when the concept of absolute responsibility is applied; specifically, that an insurer's failure to meet its contractual duties may constitute a criminal act. The courts and alternative dispute resolution methods like mediation are used to settle legal disputes. Insurance firms in Indonesia need to pay greater attention to consumer rights and adopt improved governance in order to win back the public's faith in the sector. Absolute obligation, insurance firm, failure to pay, claims made by policyholders, statutory law, are all relevant concepts here.